EXCHANGE RATE PASS-THROUGH HARGA BARANG IMPOR STUDI KASUS: SAWIT DI INDONESIA - Ruslan, Dede; Wati, Fidia; Rina, Rina; Diani, Salma; Akmalia, Uswatul (LP2M Universitas Bina Bangsa, 2025)
This study examines the exchange rate pass-through (ERPT) phenomenon on palm oil import prices in Indonesia during the period 2013-2022. The research aims to analyze the extent to which changes in the rupiah exchange rate against the US dollar affect palm oil import prices and volumes. Using multiple linear regression methods, the study evaluates the relationship between exchange rate variables and palm oil imports. Analysis results show an incomplete pass-through level, with only 16.8% of import variations explained by exchange rate changes. A correlation coefficient of 0.410 indicates a weak positive relationship that is statistically insignificant. The research concludes that external factors such as global prices, trade dynamics, and economic policies have a more dominant influence compared to exchange rate fluctuations in the context of Indonesian palm oil imports